2021
DOI: 10.1002/bdm.2247
|View full text |Cite
|
Sign up to set email alerts
|

The left digit effect in a complex judgment task: Evaluating hypothetical college applicants

Abstract: A left digit effect has been broadly observed across judgment and decision‐making contexts ranging from product evaluation to medical treatment decisions to number line estimation. For example, $3.00 is judged to be a much greater cost than $2.99, and “801” is estimated strikingly too far to the right of “798” on a number line. Although the consequences of the effects for judgment and decision behavior have been documented, the sources of the effects are not well established. The goal of the current work is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The effect is widely demonstrated in consumer price judgments (Beracha & Seiler, 2015;Lin & Wang, 2017;MacKillop et al, 2014;Manning & Sprott, 2009;Thomas & Morwitz, 2005 and has been observed in other judgment contexts where numerical information must be evaluated, such as those involving nutritional labels (Choi et al, 2019), car odometer readings (Lacetera et al, 2012), consumer product reviews (Thomas & Morwitz, 2005), and medical records (Olenski et al, 2020). With ongoing efforts to link the left digit effect in number line estimation to other domains (Patalano et al, 2022), we hope that the number line estimation task will have valuable application for assessing, understanding, and ultimately reducing the left digit effect in everyday reasoning contexts.…”
Section: Discussionmentioning
confidence: 87%
“…The effect is widely demonstrated in consumer price judgments (Beracha & Seiler, 2015;Lin & Wang, 2017;MacKillop et al, 2014;Manning & Sprott, 2009;Thomas & Morwitz, 2005 and has been observed in other judgment contexts where numerical information must be evaluated, such as those involving nutritional labels (Choi et al, 2019), car odometer readings (Lacetera et al, 2012), consumer product reviews (Thomas & Morwitz, 2005), and medical records (Olenski et al, 2020). With ongoing efforts to link the left digit effect in number line estimation to other domains (Patalano et al, 2022), we hope that the number line estimation task will have valuable application for assessing, understanding, and ultimately reducing the left digit effect in everyday reasoning contexts.…”
Section: Discussionmentioning
confidence: 87%
“…12 Leading digit effects are employed in psychological pricing, sway college admissions, and affect stock markets. [13][14][15] Leading digit bias influences clinical judgment in diverse healthcare contexts, including organ transplantation, cardiovascular surgery, oncologic care, and cigarette consumption. [16][17][18][19] We hypothesized that leading digit bias may affect the evaluation of pre-transfusion hemoglobin levels and trigger increased transfusions at clinically relevant leading digit thresholds.…”
Section: Introductionmentioning
confidence: 99%
“…The bias develops early in life, is relevant for multi‐digit numbers, and is resistant to retraining 12 . Leading digit effects are employed in psychological pricing, sway college admissions, and affect stock markets 13–15 . Leading digit bias influences clinical judgment in diverse healthcare contexts, including organ transplantation, cardiovascular surgery, oncologic care, and cigarette consumption 16–19 …”
Section: Introductionmentioning
confidence: 99%